Spreading width converted from optical model for α incident scattering - Fumimoto Toshihiro; Maeda Taiki; Ishihara Masaya; Nakamoto Riu; Ito Makoto (EPJ Web of Conferences)
We convert the optical potential in the α + 40Ca elastic scattering, which is determined so as to reproduce the diﬀerential cross section precisely, into the spreading width. This spreading width represents the decay width of the α + 40Ca resonance into the more complicated states. The conversion of the optical potential into the spreading width is achieved by the method of the absorbing boundary condition, and it is compared with the escape width of the α emission. The dissociation strength of 44Ti into the α + 40Ca continuum states is calculated to see the eﬀect of the spreading width more clearly. We also estimate the upper value of the decay width into the compound nuclear state, which is a part of the spreading width, on the basis of the formula similar to the strength function originally used in the low-energy neutron scattering.